The assessment of bone formation and bone resorption in osteoporosis: a comparison between tetracycline-based iliac histomorphometry and whole body 85Sr kinetics. - Reeve, J; Arlot, M; Chavassieux, P; Edouard, C; Green, JR; Hesp, R; Tellez, M; Meunier, P (1987)
Bone formation and resorption have been measured in patients with idiopathic osteoporosis by histomorphometry of 7.5-mm trephine biopsies and in the whole body by 85Sr radiotracer methodology and calcium balances. The studies were synchronized and most were preceded by double in vivo tetracycline labeling. Correlations between histological and kinetic bone formation indices were better when better when based on the extent of double tetracycline labels than on measurements of osteoid by visible light microscopy. Correction of the kinetic data for long-term exchange, using 5 months' serial whole body counting of retained 85Sr, improved the fit of the kinetic to the histological data. A statistical analysis of the measurement uncertainties showed that the residual scatter in the best correlations (between exchange-corrected bone formation rates and double-labeled osteoid surface indices) could be attributed to measurement imprecision alone. The exchange-corrected resorption rate correlated fairly well with iliac trabecular resorption surfaces, and using a volume referent rather than a surface referent for the histological index improved the statistical fit when patients with therapeutically accelerated bone turnover were included. A much better correlation was obtained by including osteoid volume acting as an independent predictor of bone resorption in a bivariate regression with a resorption surface index. The residual errors could then be accounted for by known measurement uncertainties. Whereas osteoid taking a double label closely predicted the kinetic rate of bone formation, further analysis suggested that osteoid that took no label or a single label was more closely related to bone resorption, presumably as a secondary result of the coupling of bone formation to bone resorption. The idea that continued bone loss in some patients is associated with defective osteoblastic bone formation is supported by the low rates found in some patients by both techniques. Heuristically these studies validate both in vivo tetracycline labeling for dynamic histomorphometry and corrections for long-term exchange in kinetic studies of bone formation, providing a quantitative framework for the design and analysis of future studies of bone remodeling in the osteoporoses.